Implementation of Digital Marketing in Efforts to Increase Sales Home Industry Custom Fishing Rod - Kristanto, Titus; Rochmah, Wachda Yuniar; Muliawati, Eka Cahya; Arief, Rachman; Ardhani, Yuniar Dwi; Syaputra, Muhammad Rashid; Aldrick, Samuel Evan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The creative industry in Indonesia, particularly the home industry, is experiencing rapid growth due to the presence of various product innovations that cater to increasingly diverse market needs. The home fishing rod industry faces difficulties in expanding the market and increasing product sales. One of the main obstacles in expanding the audience is limited marketing and promotion. Therefore, digital marketing plays a crucial role in boosting sales and broadening the market reach. The purpose of this service is to help home industry players in custom fishing rods understand and implement digital marketing strategies through social media, creating optimized websites, and using digital advertising. The methods used in this service include needs analysis, training in the use of social media, website creation and optimization, and the use of digital advertising, such as Facebook Ads. The expected result is that home industry players in custom fishing rods can compete in the global market by using the right digital marketing.